2021
DOI: 10.1002/ejoc.202100546
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted 1,3‐Dipolar Cycloaddition of Azomethine Ylides to [60]Fullerene: Thermodynamic Control of Bis‐Addition with Ionic Liquids Additives

Abstract: The cycloaddition of azomethine ylides to [60]fullerene (C 60 ) has been studied in ortho-dichlorobenzene (o-DCB) by evaluating the impact of an ionic liquid (IL) additive. The solvent effect has been addressed by evaluating the activation parameters of the cycloaddition and the boosting effect of the microwave (MW) induced dielectric heating. The IL additive plays a twofold role of stabilizing the dipolar ylide intermediate and favoring the retro-cycloaddition at high temperature regime. Under the conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Typical cycloadditions are [4 + 2], [2 + 2], and [3 + 2] reactions, but there are numerous others. [20][21][22][23] In addition, square brackets can also be used to indicate the number of electrons involved in the product formation process, rather than the number of carbon atoms. One such transformation is the Diels-Alder (DA) reaction, a thermally allowed [4 + 2] cycloaddition with the Woodward-Hoffmann symbol [π4 s + π2 s ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical cycloadditions are [4 + 2], [2 + 2], and [3 + 2] reactions, but there are numerous others. [20][21][22][23] In addition, square brackets can also be used to indicate the number of electrons involved in the product formation process, rather than the number of carbon atoms. One such transformation is the Diels-Alder (DA) reaction, a thermally allowed [4 + 2] cycloaddition with the Woodward-Hoffmann symbol [π4 s + π2 s ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present an overall picture of the mechanisms of fullerene cycloadditions with a focus on developments reported in recent years. 20,[34][35][36][37][38][39] We first discuss the mechanism of the cycloaddition for hollow fullerene, and then move on to the influence of encapsulated ions, clusters, and molecules on the mechanism and regioselectivity of the DA fullerene reaction from a theoretical standpoint. 21,[40][41][42][43] Moreover, the DA reaction of fullerene in high-spin states is also reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, 5-aryl furfural derivatives showed excellent photophysical properties, so these derivatives will be used here to functionalize C 60 . 23 Microwave irradiation (MW) is a useful tool in cycloaddition reactions and fullerene chemistry, 24,25 whereby products are formed in reasonably good yields within a few minutes. Herein, the synthesis, spectroscopic characterization, electrochemistry, and photochemical measurement of different fullerene derivatives with pyrrolidine, isoxazolone and pyrazoline rings linked to the C 60 cage are reported and their properties compared.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dipolar cycloaddition (1,3DC) reaction is a widely used synthetic tool in organic chemistry. [1][2][3][4][5][6][7] In general, the rate of 1,3DC is weakly dependent on solvent, [8][9][10] however, in several studies [11][12] a large solvent effect of up to two-three orders of magnitude is reported. The solvent effect on the 1,3DC rate coefficient is strongly dependent on the structures of dipoles: acceleration of reaction with an increase in solvent polarity was observed for azides [9] and azomethine ylides; [13] rate enhancement is also found for nitrile N-oxides in a protic solvent; whereas nitrones react faster in non-polar solvents and slower in protic ones.…”
Section: Introductionmentioning
confidence: 99%
“…1,3‐Dipolar cycloaddition (1,3DC) reaction is a widely used synthetic tool in organic chemistry [1–7] . In general, the rate of 1,3DC is weakly dependent on solvent, [8–10] however, in several studies [11–12] a large solvent effect of up to two‐three orders of magnitude is reported.…”
Section: Introductionmentioning
confidence: 99%